Proceedings of the 2014 ACM SIGMOD International Conference on Management of Data 2014
DOI: 10.1145/2588555.2593677
|View full text |Cite
|
Sign up to set email alerts
|

An application-specific instruction set for accelerating set-oriented database primitives

Abstract: The key task of database systems is to efficiently manage large amounts of data. A high query throughput and a low query latency are essential for the success of a database system. Lately, research focused on exploiting hardware features like superscalar execution units, SIMD, or multiple cores to speed up processing. Apart from these software optimizations for given hardware, even tailor-made processing circuits running on FPGAs are built to run mostly stateless query plans with incredibly high throughput. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Therefore, disk Input-Output (IO) was the dominating cost factor. Nowadays, it is possible to equip servers with several terabytes of main memory, which allows us to keep databases in main memory to avoid the IO bottleneck (Arnold et al 2014). Therefore, the performance of databases became limited by memory access and processing power (Breß et al 2014).…”
Section: Opportunitymentioning
confidence: 99%
“…Therefore, disk Input-Output (IO) was the dominating cost factor. Nowadays, it is possible to equip servers with several terabytes of main memory, which allows us to keep databases in main memory to avoid the IO bottleneck (Arnold et al 2014). Therefore, the performance of databases became limited by memory access and processing power (Breß et al 2014).…”
Section: Opportunitymentioning
confidence: 99%
“…Using large quantities of small processors to achieve similar throughputs while reducing energy footprint is becoming an increasingly important topic in Big Data research. Works on using low-power ASICs [12] and FPGAs [13] and power-efficient GPUs [14], Intel MICs [15] and SoCs [16] to process Big Data have been reported in the past few years with exciting results. Several previous works on evaluating standalone ARM-based systems for relational data query processing [17] [16] have shown that while these low profile systems are excellent for power-efficient computing under low utilization, they may not necessarily lead to significant energy saving under high utilization.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Software/hardware co-design for data sort is studied in detail in [14][15][16][17][18][19]. It is shown in [17] that the fastest known even-odd merge and bitonic merge circuits [20] are very resource consuming and can only be used effectively in existing FPGAs for sorting very small data sets.…”
Section: Introductionmentioning
confidence: 99%